The Epidemiology, Molecular, and Clinical of Human Adenoviruses in Children Hospitalized With Acute Respiratory Infections - Wen, Shunhang; Lin, Zupan; Zhang, Yue; Lv, Fangfang; Li, Haiyan; Zhang, Xueya; Lin, Li; Zhu, Hui-Hui; Xu, Zhi; Li, Changchong; Zhang, Hailin (Frontiers in Microbiology, 2021)
Introduction: Human adenovirus (HAdV) is a common pathogen in children with acute respiratory infections (ARIs). However, limited information is available regarding the association of HAdV types and outcomes in children with severe adenovirus pneumonia. Thus, this study aimed to describe the epidemiological, molecular, and clinical features of HAdV among hospitalized children with ARIs in Wenzhou, southeastern China. Methodology: Nasopharyngeal swab or sputum specimens were prospectively collected from hospitalized children with ARIs from January 2018 to December 2019. HAdV was detected using direct immunofluorescence. We performed multiplex polymerase chain reaction (PCR) combined with capillary electrophoresis to target the hypervariable region of the hexon gene to identify HAdV types 1, 2, 3, 4, 5, 7, 14, 21, 37, 40, 41, and 55. We analyzed epidemiological, molecular, and clinical data according to the HAdV types. Results: HAdVs were detected in 1,059 (3.5%) of 30,543 children tested. We included 947 children cases with monotype HAdV identified using PCR in the analysis. Phylogenetic analysis revealed that HAdV-3 (43.8%), HAdV-7 (33.6%), HAdV-2 (11.4%), and HAdV-1 (7.4%) were the predominant types. Among 550 (58.1%) children with HAdVs from December 2018 to August 2019, HAdV-3 and HAdV-7 were the main types. The main diagnoses included 358, 232, 198, and 159 cases of pneumonia, tonsillitis, bronchitis, and upper respiratory tract infection (URTI), respectively. HAdV-7 (51.1%), HAdV-3 (36.9%), and HAdV-1 (2.2%) were mainly found in children with pneumonia, while HAdV-3 (48.0%), HAdV-7 (28.3%), and HAdV-2 (10.6%) were mainly found in children with bronchitis. Among children with URTIs, the main types were HAdV-3 (49.7%), HAdV-7 (22.6%), and HAdV-2 (13.2%), and among children with tonsillitis, the main types were HAdV-3 (47.4%), HAdV-2 (22.4%), and HAdV-7 (18.5%). Overall, 101 (55.2%) children required supplemental oxygen, 15 (8.2%) required critical care, and one (0.5%) with HAdV-7 pneumonia died. Conclusion: HAdV-3, HAdV-7, HAdV-2, and HAdV-1 were the predominant types identified among hospitalized children with ARIs in Wenzhou. From December 2018 to August 2019, there were outbreaks caused by HAdV-3 and HAdV-7. There were significant differences in HAdV types among children with pneumonia, tonsillitis, bronchitis, and URTI. HAdV-7 can cause more severe pneumonia in children than HAdV-3.